2014
DOI: 10.1080/10401334.2013.857341
|View full text |Cite
|
Sign up to set email alerts
|

Implicit Bias and Its Relation to Health Disparities: A Teaching Program and Survey of Medical Students

Abstract: The recognition of bias cannot be taught in a single session. Our experience supports the value of teaching medical students to recognize their own implicit biases and develop skills to overcome them in each patient encounter, and in making this instruction part of the compulsory, longitudinal undergraduate medical curriculum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
95
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(97 citation statements)
references
References 32 publications
2
95
0
Order By: Relevance
“…In our prior study, students reported bias mitigation in their written reflections on service learning, so that bias needed to become explicit rather than remain implicit [8]. However, a course to learn about implicit bias still left 22% of medical students able to deny that implicit bias might affect some of their clinical decisions and behaviors [15,16].…”
Section: Introductionmentioning
confidence: 91%
“…In our prior study, students reported bias mitigation in their written reflections on service learning, so that bias needed to become explicit rather than remain implicit [8]. However, a course to learn about implicit bias still left 22% of medical students able to deny that implicit bias might affect some of their clinical decisions and behaviors [15,16].…”
Section: Introductionmentioning
confidence: 91%
“…Most existing educational proposals in a healthcare context have therefore focused on encouraging students to take the IAT test for themselves and subsequently to engage in small group discussions on the nature of implicit biases (Teal et al, 2010;Hernandez et al, 2012;Gonzalez et al, 2014). The authors of these programmes recognise the modest efficacy of these educational interventions.…”
Section: Existing Interventionsmentioning
confidence: 99%
“…Prompted by recognition of these issues, some new educational interventions have been developed which aim to mitigate the effects of unconscious or implicit biases in healthcare provision (Teal et al, 2010;Stone and Moskowitz, 2011;Hernandez et al, 2012;Gonzalez et al, 2014). These proposals, although welcome, suffer from serious limitations.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing patient‐perceived self‐efficacy in interacting with physicians could improve ethnic minority women's trust in providers and decrease psychological consequences. Additionally, requiring implicit bias training among providers is important as it teaches self‐awareness of biased attitudes and behaviors and strategies for engaging minority patients in a thoughtful, respectful manner …”
Section: Discussionmentioning
confidence: 99%